The Effect of PALAR-Assisted MID on Students' Mathematical Communication Ability and Self Confidence - Zalmira Aidina Barus; Tanti Jumaisyaroh Siregar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to determine the effect of the Meaningful Instructional Design learning model assisted by PALAR Media on students' mathematical communication skills and self-confidence. The method used by the researcher is a quantitative research method, with a quasi-experimental research model with a Pretest-Posttest Control Group Design research design. The data collection technique used is a test of mathematical communication skill sand a self-confidence questionnaire. Data analysis techniques used are normality test, homogeneity, and t-test. The results of theresearch are: (1) there is an effect of the PALAR media-assisted Meaningful Instructional Design learning model on students' mathematica lcommunication skills; (2) there is an influence of the PALAR media-assisted Meaningful Instructional Design learning model on students' self-confidence.